Visual-MIMO for Software-Defined Vehicular Networks - Ho Kwon, Tae; Eun Kim, Jai; Soo An, Ki; Saha, Rappy; Doo Kim, Ki (International Journal of Engineering and Technology, 2018)
The paradigm of software-defined network (SDN) is being applied to vehicle scenarios in order to eliminate this heterogeneity of vehicular network infrastructure and to manage packet flow in an application- and user-centrically flexible and efficient manner. However, owing to the random mobility of vehicles and the unpredictable road communication environment, efficient vehicle-based SDN development needs further research. In this study, we propose the concept of a sub-control plane for supporting and backing up, at the data plane level, various functions of the control plane, which plays a key role in SDN. The sub-control plane can be intuitively understood through the image processing techniques used in color-independent visual-MIMO (multiple input multiple output) networking, and the function of the control plane can be backed up through various vehicle-based recognition and tracking algorithms under the situation of disconnection between the data plane and the control plane. The proposed sub-control plane is expected to facilitate efficient management of the software-defined vehicular network (SDVN) and improve vehicular communication performance and service quality.Â Â